Concordance of diffusion tensor imaging alterations with EEG lateralization in MR negative refractory temporal lobe epilepsy (Annals of Medical Research, 2021)
Aim: In this study, we aimed to investigate the occult microstructural changes in both temporal lobes and their localization concordance with electroencephalogram (EEG) lateralization side in MR negative refractory temporal lobe epilepsies using diffusion tensor imaging (DTI).Material and Methods: Clinical files of 200 adult patients diagnosed with temporal lobe epilepsy and followed by neurology department were reviewed. A total of 32 patients who had uncontrolled seizures despite antiepileptic medication and had normal MR findings were included in the study. Using DTI data, symmetric region of interests (ROIs) were replaced on each temporal white matter to calculate parameters including fractional anisotropy (FA), radial diffusivity (RD) and axial diffusivity (AD). Mean values of each of these parameters were compared between the epileptogenic lateralization side on (EEG) and opposite temporal lobe.Results: FA and RD values were significantly different on lateralization side compared to normal side, whereas AD value showed no significant difference between two sides.Conclusion: The subtle microstructural abnormalities which cannot be discerned on routine conventional MRI practice in brains of refractory TLE patients can be revealed by DTI. The localization of these DTI abnormalities mostly shows concordance with the lateralization side on EEG. Awareness of the existence and degree of these alterations may be useful in determining medical treatment strategies or may be a guide in planning blind antiepileptic surgery.
Keywords: Diffusion tensor imaging; EEG; temporal lobe epilepsy